(untitled) (Fiep Bulletin - online, 2014)
Back pain is a common problem in the adult population, and it is becoming a serious health problem among adolescents. The aim of this study was to investigate the association of some components of physical fitness, with the prevalence of nonspecific low back pain (NLBP) in school children and adolescents. The sample consisted of 149 subjects, from 6th to 12th grade, 86 female (58%) and 63 male (42%) with a mean age of 13.5 ± 1.8. The evaluation comprehended symptoms of pain, functional disability of pain through the Roland-Morris Disability Questionnaire (RMDQ), body composition by anthropometric measurement, motor evaluation (flexibility and muscular strength) and the aerobic followed the protocol defined by Fitnessgram ® . The sample was divided into 2 groups: "With Nonspecific Low Back Pain" (with NLBP) and "Without Nonspecific Low Back Pain (without NLBP). Statistical procedures consisted of descriptive analysis, using means and standard deviations (M ± SD) for continuous variables (BMI, trunk extension, sit-and-reach left and right abdominal, shuttle test and RMDQ). The confidence interval was 95%. The MANOVA test was performed for the comparison of categorical variables between groups. The main results showed that the group with NLBP had statistically significant lower values ??for the variables of flexibility (the lower right and left limbs), abdominal strength / resistance, trunk extension and shuttle test, and higher values ??in the Rolland-Morris test (P <0.5).(*) All procedures reported are in accordance with the Declaration of Helsinki, 1975, and obtained a favorable opinion of the Scientific Committee of FCDEF (Faculty of Sport Sciences and Physical Education University of Coimbra) for its realization.